The Diversity of Major Insect Pests at Sugarcane Development Center In Dompu Distrcit, West Nusa Tenggara - Muhammad Sarjan; Muchlis Muchlis; Irwan Muthahanas (Pascasarjana, Mataram University, 2021)
Sugar cane (Saccharum officinarum Linn.) is a tropical plant that is very important because it can be used as one of the raw materials for making sugar. The development of sugar production in the last ten years has decreased by around 1.8% per year, this is due to several factors, one of which is due to the attack of sugarcane insect pests. Therefore, research was conducted to find out the diversity of important insect pests in sugarcane plants in the center of sugarcane development in the Dompu District. This research was conducted at the Pekat Sub District of Dompu District, West Nusa Tenggara. The method used is a descriptive method with data collection techniques directly and indirectly in the field at a number of observation points. Based on the observations there were 5 species of insect pests in the research area such as Valanga nigricornis, Locusta migratoria, Ceratovacuna lanigera, Scirchopaga nivella F., and Lepidiota stigma. Insect pests with the highest population and dominance are Ceratovacuna lanigera with an average population of 70 insect/plant and a domination index is 0 .199808. Locusta migratoria has a level of damage with criteria for moderate attack intensity, it is found in sugarcane plants aged 3 months. The results of this study indicate that Scirchopaga nivella F. and Lepidiota stigma F. insect pests have the potential as important pest insects on sugarcane crops